Hint As A Means Of Verification And Inspection Decision In Subsidized Fertilizer Corruption (Case Study Case Number 45 / Pid.Sus-TPK / 2016 / PN SMG) - Ardi Sanditya; Sri Endah Wahyuningish (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2019)
The Definitive Plan for Subsidized Fertilizer Needs (RDKK) is the first base for the formulation of subsidized fertilizer needs at the farmer group level. The fact that the planning and distribution of subsidized fertilizers up to the farmer level still contains serious problems and raises corruption-prone work areas. This journal aims to identify and explain the instructions as a means of proof and decision in the examination of the crime of corruption Subsidized fertilizer. The method used in this paper is descriptive qualitative approach with a normative Juridical. This study Refers to the corruption case Number 45/Pid.Sus-TPK / 2016 / PN SMG. In general, the narrative of the case contains the Defendants in the crime of corruption Subsidized fertilizer, who were charged with the primary indictment Article 2 paragraph (1) in conjunction with Article 18 of Act Number 31 of 1999 as Amended by Act Number 20 of 2001 in conjunction with Article 55 paragraph (1) 1 of the Criminal Code. The guideline is used as a means of proving and examining cases of Subsidized fertilizer corruption cases having a scheme: (1) Compiling sources of evidence in the form of witness Testimonies, letters and statements of the defendant (2) Interpreting the cues in the guidelines through the explanation of legislation related to the context of corruption, the view of legal experts, jurisprudence in the same case and (3) The panel of judges decides the case in accordance with the facts of investigation and trial so that the judge makes a decision of legal force,Keywords: Instructions; Evidence; Corruption